Pengaruh Price, Store Image Terhadap Perceived Value Dan Purchase Intention Sebagai Variabel Moderasi Di Persebaya Store Cabang Sidoarjo - Nurul Shabrinannisa; Muhammad Ridwan Basalamah; Eris Dianawati (UNIVERSITAS ISLAM MALANG, 2022)
Abstract The retail industry is a growing industry in Indonesia, one of the retail industries in Indonesia is the Distribution Outlet or commonly known as Distro. In this increasingly competitive market condition, the retail industry needs to implement a strategy that must be properly designed, so that it will become a competitive advantage for retailers in winning the competition. One of the strategies used today is that the seller is the owner of the brand (brand) meaning the store sells and distributes its own brand of products. It is intended that consumers can only buy the store's brand. This study aims to examine and analyze the effect of price, store image, on perceived value and purchase intention of consumers of Persebaya Store Sidoarjo. The sampling technique used the Malhotra formula by purposive sampling. The sample used as many as 85 respondents who live in Sidoarjo. The data collection tool used is a questionnaire. The data analysis technique used is the Survey Program. The results of this study show the results directly and indirectly, namely Store Image has a direct effect on Perceived Value, while indirectly or through the Moderation variable Purchase Intention has no effect on Perceived Value. Keywords: Price, Store Image, Perceived Value, Purchase Intention